1978
DOI: 10.1161/01.res.42.5.637
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear proteins in the heart of the cardiomyopathic Syrian hamster. Phosphorylation of phenol-soluble nonhistone proteins.

Abstract: We examined incorporation of 32 P into phenol-soluble nonhistone nuclear acidic proteins (NHNP) obtained from myolytic, hypertrophic, and failing phases of hamster cardiomyopathy. NHNP from these dystrophic hamster hearts were phosphorylated much less than their controls, despite a 9-fold increase in uptake of 32 P into their nuclei. After fractionation of NHNP by isoelectrofocusing polyacrylamide gel electrophoresis, two major fractions focusing from pH 6.0 to 6.2 and 6.6 to 6.8 were highly phosphorylated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…26 and 27) and it has recently been suggested that variations in the degree of phosphorylation of ribosomal proteins may induce conformational changes in the ribosomes (28). It may also be worth mentioning that, in dystrophic hamsters, variations in the degree of phosphorylation of histone and nonhistone nuclear chromosomal proteins have been observed (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…26 and 27) and it has recently been suggested that variations in the degree of phosphorylation of ribosomal proteins may induce conformational changes in the ribosomes (28). It may also be worth mentioning that, in dystrophic hamsters, variations in the degree of phosphorylation of histone and nonhistone nuclear chromosomal proteins have been observed (29,30).…”
Section: Discussionmentioning
confidence: 99%